Acute graft versus host disease 1976–2020: reduced incidence and predictive factors - Di Francesco, Alessandra; Raiola, Anna Maria; Dominietto, Alida; Di Grazia, Carmen; Gualandi, Francesca; Van Lint, Maria Teresa; Bregante, Stefania; Chiusolo, Patrizia; Laurenti, Luca; Sora, Federica; Giammarco, Sabrina; Metafuni, Elisabetta; et al. (Frontiers in Medicine, 2024)
We studied the incidence of acute graft versus host disease (GvHD) and its outcome in three consecutive time frames, in 3120 patients allografted in two transplant Centers between 1976 and 2020. The median age increased over the 3 periods from 32 to 54 years (p<0.00001). The median day of onset of GvHD in the 3 periods was day +14, day +16 and day +30 respectively (p<0.0001). The cumulative incidence (CI) of GvHD grade II-IV in the 3 periods was 47%, 24% and 16% respectively (p<0.00001). The CI of GvHD grade III-IV was 13%, 5%, 4% (p<0.001).significant predictive factors for GvHD II-IV, on top of year of transplant, were antithymocyte globulin (ATG) (RR 0.67, p>0.001); post transplant cyclophosphamide (PTCY) (RR 0.41, p<0.001), a family mismatched donor (RR 1.31, p=0.03) a matched unrelated donor (RR 2.1, p<0.001), an unrelated mismatched donor (RR1.8, p=0.001), donor age above 40 years (RR 1.27, p<0.001), hematological malignancy -as compared to aplastic anemia (RR 2.3, p<0.001). When selecting only grade II GvHD, in a multivariate analysis, there was a significant reduction of transplant related mortality (TRM) for patients grafted in 2001-2010 (RR 0.62, p<0.0001) and for patients grafted in 2011-2020 (RR 0.35, p<0.0001) as compared to grafts before year 2000. Similar reduction in time was seen for patients with GvHD grade III-IV. In conclusion we show improved prevention of acute GvHD with time, together with a significant delay of onset of the disease. Treatment of GvHD has also improved over time.